The Role of the Family in Building Children's Character on Religious Development in Tanjung Baru Village - Khotimah, Nurul; Setiawan, Dedi; Rahmawati, Yuning Eka (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research aims to examine the role of the family in developing children's religious character in Tanjung Baru Village, West Lampung. In the era of modernization, there is a shift in traditional values that influence parenting and education patterns in the family. The family has a crucial role as the first institution that shapes character and instills religious values in children. This research uses a qualitative method with a qualitative descriptive approach, namely collecting data through in-depth interviews, participant observation and documentation. The research subjects were families with children under 11 years old in Tanjung Baru Village. The results of the research show that families in Tanjung Baru Village apply several strategies in developing children's religious character, including through direct teaching, providing role models, habituation in daily life, motivation, and enforcing rules. Direct teaching involves instilling religious values through home learning, such as teaching prayers and reading the Koran. Parents provide role models through attitudes and behavior that reflect religious values. Habits are implemented through religious routines, such as congregational prayers and attending recitations. Motivation is given in the form of appreciation for children's positive behavior, while enforcement of rules is carried out to form discipline and religious responsibility. However, this research also found that there are challenges in developing children's religious character, such as the influence of the social environment, limited access to formal religious education, and changes in lifestyle due to modernization. To overcome these challenges, parents are trying to strengthen communication, increase involvement in religious activities, and collaborate with formal educational institutions and religious communities.